“Ilumina o país em que nascestes” – instrução e civilização na imprensa goiana: A Matutina Meiapontense (1830 – 1834) - Ribeiro, Tatiana Sasse Fabiano (2016)
The dissertation “Ilumina o país em que nascestes” – Instruction and Civilization at the Goiana Press: A Matutina Meiapontense (1830 – 1834) is set in the Research Topic “Estado, Política e História da Educação”, of the Post-Graduation Program in Education of the Federal University of Goiás – School of Education. The aim of the documental research is locating in the first periodic from the state of Goiás, hints about the education of Goiás in the beginning of XIX century. Thus, with the non-official press as the main source, we intend to contribute with the studies and researches about the theme of the history of the goiana education. For that, we have resorted to the newspaper A Matutina Meiapontense, the first goiano periodic to configure a space of dispute for power and legitimation of interests of the group behind this initiative. That newspaper circulated around the province of Goiás between the years of 1830 and 1834, and it is available at the Historical Archive of Goiás and also in the internet. The research was accomplished under a theoretical and methodological foundation of the Cultural History. On the pages of the A Matutina we can find valuable elements to uncover the goiano scenario in the first years of the independent Brazil. Some textual modalities can be found on this periodic such as proceedings of governmental meetings, extracts of texts that were taken from other periodic, correspondences, announcements, discourses signed by the editor and others. They are related to some themes, especially politics; however they span aspects of the construction of a nation in course. According to education, we can find references to the schools creation; provision; teacher development and public service exams; the importance of education and questions of everyday school, such as didactic material and teaching methods. The results, in addition to contributing for the local education history, allows us to refute the common place of the demarcated historiography of Goiás in the XIX century, as a decadent place, flagged by the stigma of delay, distance and lack of interest for education.